VD_FINDINFO ML / 2013 / 328 vom 5. Dezember 2013 - VD Tribunal cantonal (2013)
DÉCISION DE TAXATION, SOLIDARITÉ PASSIVE, PRESCRIPTION, MAINLEVÉE DÉFINITIVE, TITRE DE MAINLEVÉE | 143 CO, 144 CO, 13 al. 1 LI, 170 al. 3 LI, 238 al. 1 LI, 238 al. 2 LI, 80 al. 2 ch. 2 LP, 81 al. 1 LP